Statistics - Owen, Frank; Jones, Ron (London : Pitman, 1990)
Covers all aspects of statistics likely to be needed in business, new emphasis on computing and the use of spreadsheet templates.
Includes index
uaj 06/05/2015
Loan
Keywords: Mathematical statistics; Statistics